2012
DOI: 10.1177/2319510x1200800203
|View full text |Cite
|
Sign up to set email alerts
|

Global Financial Crisis and Stock Market Integration: A Study on the Impact of Global Financial Crisis on the Level of Financial Integration between the US and Indian Stock Markets

Abstract: This article, using the daily returns of the indices of US (S&P 500) and the Indian stock markets (CNX S&P Nifty), examines the impact of the global financial crisis on the level of financial integration between the US and Indian stock markets from March 2005 to November 2010. The article also analyses the existence of cointegration and dynamic relationship between the two indices during the pre-crisis, crisis and post-crisis periods, and in the last five years, using the Johansen Cointegration analysis and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…They explore the dynamic relationship between the two indices using Johansen co-integration and the vector auto regression (VAR) model. All four periods (Gangadharan and Yoonus, 2012) found no link. The Indian stock market returns show a lot of US–India feedback, but the US stock market returns show a little reaction.…”
Section: Literature Reviewmentioning
confidence: 94%
“…They explore the dynamic relationship between the two indices using Johansen co-integration and the vector auto regression (VAR) model. All four periods (Gangadharan and Yoonus, 2012) found no link. The Indian stock market returns show a lot of US–India feedback, but the US stock market returns show a little reaction.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Additionally, Kenourgios et al (2016) found the Islamic equities and bonds provide a hedge against risk and instability during the crisis period. Other findings uncover that the GFC exert a negative impact on Pakistani and Indian markets (Ali & Afzal, 2012), on the level of integration between the US and Indian markets (Gangadharan & Yoonus, 2012).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Numerous studies have tried to capture the linkages between the international financial markets comprising equity, debt and foreign exchange markets. For instance, Ismail and Rahman (2009), Diebold and Yilmaz (2009) and Gangadharan and Yoonus (2012) captured the linkages existing between the international equity markets. There are some studies that have also tried to account for the linkages existing between the international bond markets, like Yang (2005).…”
Section: Literature Reviewmentioning
confidence: 99%